2002
DOI: 10.1159/000065252
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Visual Environment on the Postural Stability in Healthy Older Women

Abstract: Background: A poor postural stability in older people is associated with an increased risk of falling. It is recognized that visual environment factors (such as poor lighting and repeating patterns on escalators) may contribute to falls, but little is known about the effects of the visual environment on postural stability in the elderly. Objective: To determine whether the postural stability of older women (using body sway as a measure) differed under five different visual environment conditions. Methods: Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 15 publications
4
21
0
Order By: Relevance
“…Therefore, we conclude that very low level of ambient illumination altered postural steadiness but significantly less so than did both of the no vision conditions. These results agree with those of Simoneau et al [20] who reported a minimal effect of dim light on postural sway (from 2.6 to 11 per cent for different time domain variables) and the results of Brooke-Wavel et al [6] who reported increased sway in dim light. The visual referencing differed between our study and that of Brooke-Wavel et al [6] in terms of the spatial referencing markers; in our study, a single reference point was placed in front of the participants, while Brooke-Wavel et al [6] used vertical lines to structure the environment.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, we conclude that very low level of ambient illumination altered postural steadiness but significantly less so than did both of the no vision conditions. These results agree with those of Simoneau et al [20] who reported a minimal effect of dim light on postural sway (from 2.6 to 11 per cent for different time domain variables) and the results of Brooke-Wavel et al [6] who reported increased sway in dim light. The visual referencing differed between our study and that of Brooke-Wavel et al [6] in terms of the spatial referencing markers; in our study, a single reference point was placed in front of the participants, while Brooke-Wavel et al [6] used vertical lines to structure the environment.…”
Section: Discussionsupporting
confidence: 92%
“…The illuminance in the dark room at the gaze fixation point was estimated to be 0.25 lx. This is the lowest level of illumination that has been reported (3 lx: [3], [13] and [20], 1 lx: [6]). It seems that the amount of light provided in this condition was not sufficient for accurate visual referencing and resulted in increases in postural sway.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations